The evidence for cardiothoracic surgery - Treasure, Tom (Tfm Pub., 2005)
With an emphasis on randomly controlled trials when available, the 28 contributed chapters present evidence for standard operations and innovative treatments for cardiothoracic disease, including lung cancer, bronchopulmonary tumors, re-vascularization, and indications for cardiac transplantation. The introductory chapter presents the case for evidence-based medicine and its application in this surgical specialty. Chapters include evidence summary tables, surgical recommendations, and further reading.